2015
DOI: 10.1155/2015/418585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Milling Conditions on the Hydriding Properties of Mg‐C Nanocomposites

Abstract: Mg75 at.%, CB25 at.% (CB: carbon black) composites were synthesized at different ball milling conditions (milling energy, milling duration, and environment) and their hydriding properties were characterized by high-pressure DSC. The SEM observations revealed that the samples consist of 5–15 μm Mg particles, surrounded and in some cases coated by carbon particles. X-ray diffraction analysis showed that the Mg phase of all as-obtained composite powders is nanocrystalline with average crystallite size in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…A high rotation speed leads to particle friction and destruction of CNTs, which contributes to the formation of smoother particles [35,36]. However, such high rotational speeds can lead to a decrease in the concentration of carbon/graphite particles on the surface of MgH 2 particles due to their incorporation into the particles and because of the formation of amorphous carbon [37,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high rotation speed leads to particle friction and destruction of CNTs, which contributes to the formation of smoother particles [35,36]. However, such high rotational speeds can lead to a decrease in the concentration of carbon/graphite particles on the surface of MgH 2 particles due to their incorporation into the particles and because of the formation of amorphous carbon [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…However, the decrease in the activation energy of desorption in this case is insignificant and is practically within the error limits. A decrease in the activation energy of hydrogen desorption, as well as the temperature of hydrogen desorption, can occur due to the influence of several factors, such as due to the high thermal conductivity of CNTs [43] and their incorporation into magnesium particles, which allows hydrogen atoms to be diffused more easily from the bulk of the material [37,44]. It can also be related to the distribution of metal catalysts contained in nanotubes [20].…”
Section: Resultsmentioning
confidence: 99%
“…The composites milled in dry conditions showed that the hydriding kinetics improved significantly at low temperatures. The melted composites showed a rapid deterioration in capacity during the cycling period in the presence of heptane, which showed an efficient carbon coating process [44].…”
Section: Mechanical Millingmentioning
confidence: 99%
“…The authors concluded that the addition of more than 9 wt.% of graphite to Mg-V fine powder did not lead to any further acceleration of hydrogen absorption. The newest results are reported in studies [1,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%